Navigating the Field: Exploring the Influence of Professional Identity on Employability in Chinese College Athletes with Time Management as a Mediator - Jin, Hongyin; Tu, Chiaching, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The study investigated employability dynamics among Chinese collegiate athletes, with a focus on professional identity (PI) and an analysis of time management (TM) as a mediating factor. Understanding the relationship between PT, TM, and EMT is essential for Chinese college athletes as they navigate demanding academic and athletic environments. Data was gathered from five universities involving a sample of 224 student-athletes, consisting of 142 males and 82 females. Analysed using the Statistical Package for Social Sciences (SPSS). This study examines the influence of PI on EMT results, both directly and indirectly, by analysing its impact on TM practices using the Partial Least Squares – Structural Equation Modelling (PLS-SEM) statistical package for the social sciences. The study revealed complex connections and routes, providing insight into the impact of PI on athletes' preparedness for the workforce. The study highlights the importance of developing mental toughness and improving technical skills to improve career opportunities for Chinese college athletes. The study presents a framework to help athletes effectively manage the challenges of professional travel. The article provides valuable insights into college athletes, higher education, and career development.